Category “Event” in the latest Spanish literature as exemplified by flash fiction of Andrés Neuman and Helena Cosano - Khoreva Larisa G. (Актуальные проблемы филологии и педагогической лингвистики, 2019)
Article deals with analysis of category of an event in the latest Spanish flash fiction. The relevance of the real research is caused by absence in modern literary criticism of researches on category of an event in the latest Spanish literature. In article the review of the concept “event” is given. The author of article in details considers the main characteristics of these concepts. The concept “event” in flash fiction of the modern Spanish writer Helena Cosano and the Argentina author Andres Neuman become a subject of studying. In the collections of short prose belonging to a feather of these authors the madness discourse brightly proves. The author of article shows, that this discourse creates a special communicative event, but it is not event in the true sense of the word. The Spanish culture, which during centuries existed under strong influence of Catholicism, did not see in madness any violation of any norms. In this regard the Spanish literature and culture differed from French one where the madman was considered as the person sick with a shameful disease. On the basis of the analysis of short prose of Andres Neuman and Helena Cosano the author comes to a conclusion that numerous repetition of the same motive of madness form the concept “event” that gives the chance to speak about a repetition esthetics as literary reception and, more widely, rituality of the narration as a narrative event in the latest Spanish-speaking literature